2021
DOI: 10.3390/ijms22157951
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine Methyltransferase 1 Is Essential for the Meiosis of Male Germ Cells

Abstract: Protein arginine methyltransferase 1 (PRMT1) is a major enzyme responsible for the formation of methylarginine in mammalian cells; however, its function in vivo is not well understood due to its early embryonic lethality in null mice exhibiting spontaneous DNA damage, cell cycle delays, and defects in check point activation. Here, we generated germ cell-specific Prmt1 knock-out (KO) mice to evaluate the function of PRMT1 in spermatogenesis. Our findings demonstrate that PRMT1 is vital for male fertility in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Furthermore, PRMT1-mediated histone H4R3me2a methylation is crucial for regulating cell proliferation in various organs and serves as a key regulator of normal vertebrate development and growth [ 22 ]. Studies have demonstrated PRMT1’s involvement in regulating the self-renewal of hematopoietic stem cells and normal hematopoiesis [ 23 ], as well as in the normal development of lymphocytes [ 24 , 25 ], the differentiation and proliferation of intestinal cells [ 26 ], myelin regeneration [ 27 ], and spermatogenesis [ 28 ]. Notably, the absence of PRMT1 in mice results in a significant decrease in the proliferation of palate mesenchymal cells, ultimately preventing the palatal shelves from reaching the midline and resulting in a complete cleft palate phenotype [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PRMT1-mediated histone H4R3me2a methylation is crucial for regulating cell proliferation in various organs and serves as a key regulator of normal vertebrate development and growth [ 22 ]. Studies have demonstrated PRMT1’s involvement in regulating the self-renewal of hematopoietic stem cells and normal hematopoiesis [ 23 ], as well as in the normal development of lymphocytes [ 24 , 25 ], the differentiation and proliferation of intestinal cells [ 26 ], myelin regeneration [ 27 ], and spermatogenesis [ 28 ]. Notably, the absence of PRMT1 in mice results in a significant decrease in the proliferation of palate mesenchymal cells, ultimately preventing the palatal shelves from reaching the midline and resulting in a complete cleft palate phenotype [ 29 ].…”
Section: Introductionmentioning
confidence: 99%